Evaluasi Ureum Pada Penyandang Diabetes Melitus dalam Risiko Gagal Ginjal di Bengkulu - Raden Sunita; Heru Laksono (Poltekkes Kemenkes Jakarta III, 2019)
Diabetes mellitus (DM) is a disease characterized by continuous and varied increases in blood sugar (glucose) levels due to a disturbance in the pancreas that cannot produce enough insulin. Increased glucose levels can damage the physiology of the kidneys if they exceed the threshold of kidney. DM patients who are more than 5 years old are recommended for initial screening, one of them is an urea examination. This study was a descriptive cross-sectional study design carried out at the Internal Medicine Police Hospital Dr. M. Yunus Bengkulu with 38 people with DM. Sampling using accidental sampling technique. Ureum level examination was carried out using the AU 680 Beckman Coulter Chemistry Analyzer. Results: abnormal urea levels based on the duration of DM <5 years as many as 36% and> 5 years 87%. abnormal urea levels based on regular drug consumption ie (62%) while those taking irregular drugs resulting in abnormal urea levels (50)%). abnormal urea levels based on the duration of suffering> 5 years and taking medication regularly amounted to 87% and normal urea levels amounted to 13%. Evaluation of the level of urea in patients with diabetes that exceeds the normal limit is caused by the duration of suffering from diabetes and taking medication regularly.